PENGARUH PENGGUNAAN MEDIA PUZZLE TERHADAP KEMAMPUAN MENGHAFAL AYAT AL-QUR’AN PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VIII DI MTs MIFTAHUSSALAM KOTA BOGOR - Findayani, Hanny (Aksara Public, 2019)
This study aims to find out (a) the application of puzzle media on the subjects of the Qur'an class VIII Hadith at MTs Miftahussalam, Bogor City, (b) the ability to memorize the verses of the Qur'an in learning the Qur'an VII class Hadith in Bogor City MTs Miftahussalam and (c) the influence of the use of media puzzles on the ability to memorize the verses of the Qur'an in the subjects of the 8th grade Al-Hadith in MTs Miftahussalam, Bogor City. This study uses a quantitative approach. The method used is a quasi-experimental method with pretest and posttest control group design. The population in this study were eighth grade students at Mifathussalam MTs, Bogor City. Determination of samples using sampling techniques where the entire population is sampled (census / total sampling). Based on the results of the sampling technique obtained samples of class VIII A as the experimental class and class VIII B as the control class. The results of research data analysis that has been carried out before and after treatment there are significant differences obtained by the value of t -10.559 abel t table 2.011, t table can be seen in the statistical table at a significance of 0.05 with the degree of validity (df) = nk or 50-2 = 48 Because the t-count is -10.599 ≤ ttable 2.011 and the significance is 0.05 (0.00 <0.05), then Ho is rejected and Ha is accepted. So it can be concluded that the media for the application of puzzle media in the subjects of the Qur'an in the class VIII Hadith at MTs Miftahussalam, Bogor City has an effect on the ability to memorize the verses of the Qur'an.